In Search of the Lost (Female) Dramaturgs (Itinera, 2019)
Most of the academic articles that look at the development of 20th century Italian women’s theatre begin with a discussion of the dramatic works of narrators such as Natalia Ginzburg and Dacia Maraini, or performers such as Franca Valeri and Franca Rame. In this article, I claim that an alternative path for the discovery of Italian women playwrights can be found by visiting libraries and archives and looking for women dramatists as authors of theatrical genres often considered minor: radio dramas and the educational plays. After an analysis of the two genres, I look at the careers of three women playwrights that started as writers for radio or educational plays and went on to have successful careers in TV adaptations (Anna Luisa Meneghini), children’s theatre (Gici Ganzini Granata) and the major theatre (Clotilde Masci).